Budget absorption optimization strategy of PT PLN (Persero) North Sumatra development holding unit - Sitorus, Elwis; Nasution, Fahmi Natigor; Syahyunan, Syahyunan; Irawati, Nisrul; Muda, Iskandar (Institute of Computer Science (IOCS), 2024)
This research is based on the report of budget absorption realization at PT PLN UIP SBU not being absorbed according to the plan. The aim of this study is to identify the main causes of suboptimal budget absorption and to formulate strategies to optimize budget absorption at PT PLN UIP SBU in the future. Analysis of the potential factors causing the failure to achieve the budget absorption target is conducted through discussions and interviews, followed by Likert scale interval analysis of respondent perceptions to determine the main causes of the failure to achieve the budget absorption target. Subsequently, the formulation of the selected strategy uses analysis with the Analytic Hierarchy Process (AHP) method. Based on the research results, the first priority alternative is the standardization of the completeness of budget proposal documents (detailed scope of work, timeline, Bill of Quantities along with references, field survey documentation if needed, and others). The second priority is holding regular periodic meetings with PLN Headquarters regarding budget needs and the bidding process at PLN Headquarters. The third priority is tightening monitoring and risk management evaluation for each project, followed by the fourth priority, which is holding regular meetings on the general plan for procurement unit auctions.